2018
DOI: 10.1525/elementa.276
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial-viral interactions in the sea surface microlayer of a black carbon-dominated tropical coastal ecosystem (Halong Bay, Vietnam)

Abstract: Increasing human activity has raised concerns about the impact of deposition of anthropogenic combustion aerosols (i.e., black carbon; BC) on marine processes. The sea surface microlayer (SML) is a key gate for the introduction of atmospheric BC into the ocean; however, relatively little is known of the effects of BC on bacteria-virus interactions, which can strongly influence microbially mediated processes. To study the impact of BC on bacteria-virus interactions, field investigations involving collection fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 68 publications
5
16
0
1
Order By: Relevance
“… (A) Distribution of aster-like nanoparticles (ALNs) and bacteria abundances in 16 selected stations of a tropical coastal ecosystem (Ha Long Bay-Vietnam), and (B) analyses of correlations (Spearman's product-moment correlation coefficient) between ALNs and environmental parameters which compile all sampling points. All details on Ha Long Bay (Vietnam) environment are available from Pradeep Ram et al (2018). Level of significance: * p < 0.001.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… (A) Distribution of aster-like nanoparticles (ALNs) and bacteria abundances in 16 selected stations of a tropical coastal ecosystem (Ha Long Bay-Vietnam), and (B) analyses of correlations (Spearman's product-moment correlation coefficient) between ALNs and environmental parameters which compile all sampling points. All details on Ha Long Bay (Vietnam) environment are available from Pradeep Ram et al (2018). Level of significance: * p < 0.001.…”
Section: Resultsmentioning
confidence: 99%
“…This property prompted us to explore the environmental parameters potentially affecting ALN dynamics at the spatial scale. This was achieved on 16 selected geographical stations from Ha long bay estuary in Vietnam, a highly spatially contrasted environment previously characterized by Pradeep Ram et al (2018). This spatial survey indicated significant coupling between ALN and prokaryote abundances (Figure 10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dilution did not have any significant bearing on bacterial counts. This methodology has been previously validated and adopted for reporting bacterial and viral counts in Halong Bay (Pradeep Ram et al, 2018). The mixture was incubated for 5 min, heated for 10 min at 80 • C in the dark, and cooled for 5 min prior to analysis.…”
Section: Bacterial and Viral Abundancesmentioning
confidence: 99%
“…Considering the large amounts of BC continuously entering the ocean, and especially via wet deposition, one may expect this material to impact pelagic systems (Weinbauer et al, 2017). In the atmosphere, BC is associated with other aerosols, the input of BC to the marine environment may lead to an enrichment in BCassociated elements, such as organic carbon (Willey et al, 2000;Raymond, 2005), nutrients (Mahowald et al, 2008;Kanakidou et al, 2012;Wang et al, 2015), trace metals (Paytan et al, 2009;Ito, 2013), and even pesticides (Kunz et al, 2005), potentially altering the structure and activity of phytoplankton (Paytan et al, 2009;Guo et al, 2012) and bacterial (Cattaneo et al, 2010;Mari et al, 2014;Pradeep Ram et al, 2018) communities. In addition, it has been shown that the BC introduced into marine surface waters sorbs dissolved organic matter (DOM), nutrients and small particles, and stimulate aggregation processes (Mari et al, 2014(Mari et al, , 2017a.…”
Section: Introductionmentioning
confidence: 99%